Functional Variant rs3135500 in NOD2 Increases the Risk of Multiple System Atrophy in a Chinese Population - Cao, Bei; Chen, Yongping; Zhou, Qingqing; Zhang, Lingyu; Ou, Ruwei; Wei, Qianqian; Wu, Ying; Shang, Hui-Fang (Frontiers in Aging Neuroscience, 2018)
Background: Given the overlap of clinical manifestations and pathological characteristics between Parkinson's disease (PD) and multiple system atrophy (MSA), we investigated the associations between five functional polymorphisms of nucleotide-binding oligomerization domain protein 2 (NOD2) which were associated with PD, and MSA in a Chinese population. Methods: A cohort of 431 MSA patients and 441 unrelated healthy controls (HCs) were included in the study. Five polymorphisms in NOD2, including P268S, R702W, G908R, 1007fs, and rs3135500, were genotyped. The mRNA expression of NOD2 in peripheral mononuclear cells (PBMCs) in 32 MSA patients were analyzed using RT-PCR, and the concentration of NOD2 and α-synuclein from plasma of 57 MSA patients were also measured by ELISA analysis. Results: No heterozygous or homozygous for R702W, G908R, and 1007fs were found in all the subjects. For rs3135500, differences in genotype distributions, dominant and additive genetic models, were found between MSA and HCs, and between MSA Parkinsonism (MSA-P) patients and HCs. Interestingly, patients carrying the “A” allele of rs3135500 had higher mRNA NOD2 level from PBMCs and NOD2 protein from plasma than patients without this allele (p = 0.028 and p = 0.036, respectively). In addition, we also found the concentration of NOD2 in plasma was positively correlated with the levels of NOD2 mRNA in PBMC and α-synuclein in plasma (R = 0.761 and 0.832, respectively). Conclusion: Our findings suggest that the rs3135500 variant in the NOD2 gene might increase the risk for MSA and might provide new evidence that inflammation mediated by NOD2 involved in the pathogenesis of MSA. Further association studies involving a larger number of participants, as well as functional studies, are needed to confirm our current findings.